Developing a Comprehensive Website for ‘Gore English School’: An Analytical Study - Patil, Maheshwari; Mote, Pallavi; Nanaware, Samruddhi; Todkar, Vidya; Phuge, Rupali (International Journal of Computer Sciences and Engineering, 2025)
The Gore English School Chousala website is designed to provide a centralized platform that enhances communication, accessibility, and engagement for students, parents, and staff. This project aims to streamline essential information, including academic updates, event notifications, and resource sharing, into a user-friendly and visually appealing interface. Using modern web development techniques, the site emphasizes intuitive navigation, responsiveness across devices, and an aesthetic that reflects the school’s values. Key features include interactive admission forms, real-time announcements, and a dedicated section for academic achievements. The website ensures data security and ease of access, catering to a broad audience with varying technical expertise. This initiative highlights the significance of digital transformation in educational institutions, fostering stronger connections within the school community while promoting a seamless exchange of information.